Hot flying - Motion Planet (Kuala Lumpur : Motion Planet Production, 1990)
Experience the real flying that goes on even beyond the crowd-pleasing action at the world's airshows
VCD format
Keywords: Flight in motion pictures; Air shows; Jet planes